Cox Proportional Hazard Regression for Risk Factors of Alzheimer’s Disease - Hosseinioun, Nargess (Journal of Medicine, 2019)
Background: Alzheimer’s disease is a form of dementia, mainly strikes people in their 60 and 70s. While no one cause has been determined, researchers have identified certain factors which may put people at a higher risk of developing the disease. Iran’s Alzheimer Association has announced that more than 35% of people over 80 years old suffers from this problem across the country. This paper aims to investigate modifiable risk factors of Alzheimer’s disease based on Kaplan-Meier estimator and Cox regression analysis (proportional hazard model) and to find out which factors are related to developing of this disease. Materials & methods: Residents newly admitted to nursing homes with a diagnosis of probable Alzheimer’s disease have been considered. Patients were at least 75 years of age from 9 Medicare/ Medicaid certified nursing homes of Khorasan and Tehran states and we excluded patients with a history of mental retardation, mental illness or any other long-life mental health disorders. This strategy yielded a sample of 115 patients (37 Males and 78 Females) with total death rate of 47%. Results: Our findings demonstrate that Age, Gender, Heritage, Apoplexy, Mental and Physical Activities statistically affect Survival and also Hazard Rate, In contrast, we found no link between survival duration and a history of Addiction and Blood Pressure. Conclusions: These findings have implications for clinical practice and intervention strategies in medical and public health. J MEDICINE JUL 2019; 20 (2) : 72-79